Dilemmas and future perspectives of teachers in master fellowship program in education - Sime Poma, Luis (2017)
Different fellowships programs to public school teachers have been developed in Latin-American. In Perú, this new program has been managed by Pronabec financing fellowships for teachers of different regions during 2014-2015. Thisstudy is addressed to analyze the teachers´ dilemmas faced when they applied; and, explore the future professional perspectives of this kind of teacher. The qualitative  method implies a documental analysis and survey with open answers to 20 teachers. Four types of dilemmas were identified–master versus family, master versus school, master versus another study, master versus no migration–, and eight possible futures scenarios related to the professional, academic, and unionpolitical fields.